2011
DOI: 10.1109/tmag.2010.2091418
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Evaluation of Mechanical Stress Using the Reciprocal Amplitude of Magnetic Barkhausen Noise

Abstract: This paper describes a method for detecting stress in the surface of magnetic materials, such as steels, based on the measurement of magnetic Barkhausen emissions. The paper presents a simple practical linear calibration curve that can be used to determine stress, and also provides a theoretical explanation of the reason for such a relationship. The influence of elastic tensile and compressive stresses of various magnitudes on the magnetic Barkhausen emissions was studied, with the objective of developing a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 16 publications
2
49
0
Order By: Relevance
“…By that, we show that the previously observed bulk relationship between Barkhausen amplitude and stress 15,16 can also be seen in the frequency domain. This result has practical consequences in the area of nondestructive characterization; it introduces the possibility of predicting stress at specific depths inside a magnetic material, solely by measuring the Barkhausen emissions at the surface and analyzing the results in terms of two parameters.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…By that, we show that the previously observed bulk relationship between Barkhausen amplitude and stress 15,16 can also be seen in the frequency domain. This result has practical consequences in the area of nondestructive characterization; it introduces the possibility of predicting stress at specific depths inside a magnetic material, solely by measuring the Barkhausen emissions at the surface and analyzing the results in terms of two parameters.…”
supporting
confidence: 75%
“…15,20 This relationship can be derived from an extension to the theory of ferromagnetic hysteresis. 21 The parameter hVi, being the yintercept of the frequency spectrum, represents an extrapolated mean value, which is expected to vary with stress, in a way similar to the peak envelope amplitude and RMS.…”
Section: Theorymentioning
confidence: 99%
“…The work presented in [5], reported that the vector magnetic property of the electrical steel sheet depends on the mechanical stress and the direction of the magnetic field excitation and has to be taken into account when designing the electrical machine. Moreover, the work in [6] describes a method for detecting stress on the surface of magnetic materials, such as steels, using measurements of magnetic Barkhausen emissions. These results are interesting as they put in evidence the impact of mechanical stress on the local magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…For materials with positive magnetostriction, the magnetic moments tend to align in parallel to the direction of tensile stress, and perpendicular to compressive stress. In materials with negative magnetostriction, opposite phenomena occurthe magnetic moments tend to align perpendicular to the direction of tensile stress, and in parallel to compressive stress [12,13]. The impact of uniaxial stress on the domain structure can be compared to the effect of a magnetic field with strength H σ which is equivalent to the stress…”
Section: Resultsmentioning
confidence: 99%